2007
DOI: 10.4049/jimmunol.178.1.352
|View full text |Cite
|
Sign up to set email alerts
|

Decay-Accelerating Factor Must Bind Both Components of the Complement Alternative Pathway C3 Convertase to Mediate Efficient Decay

Abstract: Decay-accelerating factor (DAF; CD55) inhibits the complement (C) cascade by dissociating the multimolecular C3 convertase enzymes central to amplification. We have previously demonstrated using surface plasmon resonance (Biacore International) that DAF mediates decay of the alternative pathway C3 convertase, C3bBb, but not of the inactive proenzyme, C3bB, and have shown that the major site of interaction is with the larger cleavage subunit factor B (Bb) subunit. In this study, we dissect these interactions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
7
39
0
Order By: Relevance
“…To test effects of C3 R102G polymorphism on convertase accelerated decay, different concentrations of sDAF, native fH and rfH1-4 were flowed over C3b 102G Bb or C3b 102R Bb-coated surfaces to catalyze rapid decay of Bb (30,31) (Fig. 3 A-C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test effects of C3 R102G polymorphism on convertase accelerated decay, different concentrations of sDAF, native fH and rfH1-4 were flowed over C3b 102G Bb or C3b 102R Bb-coated surfaces to catalyze rapid decay of Bb (30,31) (Fig. 3 A-C).…”
Section: Resultsmentioning
confidence: 99%
“…To explore molecular mechanisms underlying differential hemolytic activity, formation and natural decay of the AP C3 convertase was analyzed using surface plasmon resonance (SPR) (Biacore). AP C3 convertase formed on Biacore chips replicates natural convertase: it is labile, cleaves C3, deposits nascent C3b, and is regulated by decay accelerators (30,31). Either fB alone, or fB and fD together, were flowed over each C3b variant.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that DAF interacts with C3bBb through major sites in SCR2 and SCR4. It has been suggested that the high affinity of binding to Bb via SCR2 (compared to little or no binding to fB), concentrates DAF on the active convertase, whereas the weaker interactions through SCR4 with C3b directly mediate decay acceleration (28).…”
Section: Functional Implications Of the 3d Structures Of C3bb(ni 2؉ )mentioning
confidence: 99%
“…5), suggesting a functional role for module 1 in CP DAA. Earlier examination of CP DAA by human complement regulators suggested that dissociation of the protease subunit from the convertase is a result of binding of the regulators to C4b and C2a, followed by a conformational change in the von Willebrand factor type A (vWFA) domain (45,47,63,64). More recently, it has been suggested that dissociation of the convertases could also be a result of displacement of the protease subunit by the regulator owing to a competition posed by the regulator for the protease interaction site on the noncatalytic subunit of the convertase (51).…”
Section: Vcp Domains Critical For Daasmentioning
confidence: 99%